Wirausaha Berbasis Literasi Website ‘REKAN Publikasi’ dalam Rangka Mempublikasikan Aset Intelektual di Perguruan Tinggi - Andrian Febrianto; Raditya Abel Yudanta; Raja Mahasakti Surya Bumi; Muhammad Arif Alamsyah Tanjung; Muhammad Sulton Maulana; Kundharu Saddhono (Universitas 45 Surabaya, 2023)
Advances in technology create convenience as well as considerable challenges and even create global competition, one sector that has major challenges is the education sector. Entrepreneurship is one of the subjects that can answer this challenge, with an innovation and by utilizing technology through entrepreneurship, one of which is creating website-based business products. In the research process of making this website using research and development methods (research and development). In order to realize the website, it is necessary to go through several stages in making the website, in the form of: (1) the needs analysis stage; (2) the manufacturing or design stage; (3) trial and development stage; and (4) dissemination stage to users. In the process, these stages will be explained and elaborated coherently to get the results of the research.